Cypermethrin's Consequences on the Male Reproductive System of Swiss Albino Mice - Abusrer, Salma; Elkhoja, Ayat (AlQalam Journal of Medical and Applied Sciences, 2026)
Infertility is a prevalent issue impacting millions of individuals of reproductive age globally. The reduction in male fertility has been linked to various factors, including exposure to environmental pollutants like pesticides. Cypermethrin, a type II synthetic pyrethroid insecticide commonly used in Libya, is the focus of this study, which aims to evaluate its effects on the male reproductive system in mice. The research involved three groups of adult male Swiss albino mice (Mus musculus), each consisting of eight individuals. The control group received distilled water, while the treatment groups were administered cypermethrin at doses of 65.7 mg/kg (CYP I) and 93.86 mg/kg (CYP II) of body weight (bw). All treatments were delivered orally via gavage over a period of 28 days. At the end of the experiment, measurements were taken for body and testicular weights, as well as serum levels of testosterone, luteinizing hormone (LH), and follicle-stimulating hormone (FSH). Additionally, semen parameters, including sperm count, motility, and morphological abnormalities, were assessed. Histopathological evaluations of testicular tissue were conducted using histological cross-sections. Results indicated no significant differences in body weight between the treatment and control groups. However, the higher dose (CYP II) led to a marked reduction in testicular weight, sperm count, motility, and normal sperm morphology, alongside all histopathological criteria, Johnsen's score, testosterone, and LH levels, while FSH levels increased. These findings suggest that cypermethrin induces testicular toxicity and adversely affects male fertility in mice